PROBLEMATICS OF ONLINE LEARNING IN INDONESIA - Nur, Haerani; AR, Hasniar; Damayanti, Eka; Hadisaputra, Hadisaputra (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract: This study aims to explore the dynamics of online learning in Indonesia and reflect on the effectiveness of the teaching and learning processes. A question of interest is: How have people adapted to these changes? This was investigated via a systematic literature review (SLR), which involved 30 journal articles. Google Scholar was the source of these articles. The literature review reveals that teacher and lecturer readiness, student independence, availability of facilities, and parental support are the principal factors in determining the effectiveness of online learning across all education levels. The adaptation process is marked by deliberate attempts to enhance teaching skills (from teachers and lecturers), undergo the learning process (from students and university students), provide online learning facilities (from education providers such as schools and colleges), and offer support (from parents). Failure to adapt to any of these parties could potentially create issues that affect the effectiveness of online learning. The findings of this research can serve as a foundation for initiating programs aimed at improving the quality of online learning in Indonesia. Abstrak: Penelitian ini bertujuan untuk mengeksplorasi dinamika pembelajaran online di Indonesia dan merefleksikan efektivitas proses belajar mengajar. Pertanyaan yang menarik adalah: Bagaimana masyarakat beradaptasi terhadap perubahan ini? Hal ini diselidiki melalui tinjauan literatur sistematis (SLR), yang melibatkan 30 artikel jurnal. Google Cendekia adalah sumber artikel ini. Tinjauan literatur mengungkapkan bahwa kesiapan guru dan dosen, kemandirian siswa, ketersediaan fasilitas, dan dukungan orang tua merupakan faktor utama dalam menentukan efektivitas pembelajaran daring di semua jenjang pendidikan. Proses adaptasi ditandai dengan upaya yang disengaja untuk meningkatkan keterampilan mengajar (dari guru dan dosen), menjalani proses pembelajaran (dari pelajar dan mahasiswa), menyediakan fasilitas pembelajaran online (dari penyelenggara pendidikan seperti sekolah dan perguruan tinggi), dan menawarkan dukungan (dari orang tua). Kegagalan beradaptasi dengan salah satu pihak tersebut berpotensi menimbulkan permasalahan yang mempengaruhi efektivitas pembelajaran online. Temuan penelitian ini dapat menjadi landasan untuk memulai program yang bertujuan meningkatkan kualitas pembelajaran online di Indonesia.